PENINGKATAN PENGETAHUAN IBU HAMIL TERHADAP KEHAMILAN RESIKO TINGGI - Deby Meitia Sandy (IKesT Muhammadiyah Palembang, 2022)
A high risk pregnancy is a pregnancy that will cause greater danger and complications to both the mother and the fetus to be conceived during pregnancy, childbirth or the postpartum period. More than 90% of maternal deaths are caused by obstetric complications during pregnancy, childbirth and the puerperium. The causes of maternal death are bleeding, hypertension, infection, circulatory system disorders, and metabolic disorders. The purpose of this activity is to increase the knowledge of pregnant women about high risk pregnancies in the